2017
DOI: 10.7860/jcdr/2017/22904.9401
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Alloimmunization and Autoimmunization among Blood Donors and Recipients visiting a Tertiary Care Hospital

Abstract: Introduction: The ultimate aim of pretransfusion testing is the acceptable survival of donor red cells in recipient's body and antibody detection plays a critical role in achieving the same. The cornerstone of antibody detection method is detecting an unexpected antibody as against the expected antibodies of ABO blood group system. Autoantibodies can also interfere with the detection of clinically significant alloantibodies. Aim:To study the frequency of alloantibodies and autoantibodies in the healthy blood d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
2
8
1
Order By: Relevance
“…A study conducted in Southern Thai population 8 showed the following antibodies, frequency-wise as most common - anti-Mi a , anti-E, anti-Le a , anti-c and anti-Le b . In the present study, only 30 donors (0.018%) had autoantibody as also reported earlier by Kaur et al (0.5%) 6 and Tiwari et al (0.04%) 18 . In the present study, though we took detailed history about the aetiology of antibody formation, many alloantibodies were found in male blood donors.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A study conducted in Southern Thai population 8 showed the following antibodies, frequency-wise as most common - anti-Mi a , anti-E, anti-Le a , anti-c and anti-Le b . In the present study, only 30 donors (0.018%) had autoantibody as also reported earlier by Kaur et al (0.5%) 6 and Tiwari et al (0.04%) 18 . In the present study, though we took detailed history about the aetiology of antibody formation, many alloantibodies were found in male blood donors.…”
Section: Discussionsupporting
confidence: 91%
“…The higher rate of alloimmunization in females could be attributed to antigenic exposure during pregnancies. Other studies on healthy blood donors showed frequency of alloimmunization from 0.05 to 4.0 per cent 4 5 6 7 8 9 10 11 . In our study, most frequent alloantibodies identified were of MNS blood group system.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…(0.05%). [ 14 15 ] This could be because of the fact that solid-phase testing has increased sensitivity and may detect weak autoantibodies that other method may miss. [ 12 ] As per our institutional policy, DAT-positive blood units were discarded.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study from a different transfusion center in the same region, 0.06 percent of the donors (4 of 6350) were found to be alloimmunized. 10 Studies from the national capital region of India quoted the incidence of unexpected antibodies among Indian donors to be in the range of 0.01 to 0.11 percent. 3,11,12 In our study, the most frequent alloantibodies identified were of the Lewis blood group system (17 of 25 [68%] in 14 of 19 alloimmunized donors), the second most common alloantibodies belonged to the Rh blood group system (4 of 25 [16%] in 3 of 19 alloimmunized donors), followed by those of the MNS blood group system (3 of 25 [12%] in 2 of 19 alloimmunized donors), and anti-K in one donor (1 of 25 [4%]).…”
Section: Discussionmentioning
confidence: 99%